Destination Branding - Application of Product Marketing Principles to Place Marketing in the ‘GREAT Britain – You’re Invited’ Marketing Campaign - Sakhalkar, Varuni (2012)
With increasing competition, destinations are vying with each other to create a positive image and personality to gain a competitive advantage. Consumers today are better connected and well informed due to the online travel revolution. They play a more active role and technology players like Facebook are becoming a necessary partner for the travel industry. This high internet usage and increased interaction over social media changes the way branding and marketing is managed and executed. The power of branding can be seen across varied industries and the tourism sector is no different. So far there have been extensive research and studies about marketing principles and their application to tangible goods and intangible services. There has also been a growing interest in the application of these principles to successfully brand tourist destinations, regions, cities and in fact entire countries. This report looks at what has been published about branding a destination vis-à-vis branding a product; its complexity and limitations shall be explored on the basis of the nature of the industry and the current industry analysis. The importance of studying this particular topic was felt after carrying out a thorough industry analysis for the travel industry in UK, which provided insight into the current scenario and difficulties being faced by firms within the sector. In these times of economic instability it has become all the more competitive and essential for destinations to be branded in order to highlight their unique selling proposition; which could potentially attract more travellers and contribute positively towards the industry revenue stream as well as the region’s GDP. Since London won the bid to host the 2012 Olympic Games, there has been a conscious effort and plan to utilise this globally popular event to showcase Britain as a favourable tourism and business destination. Various marketing plans have been put in place by the tourism bodies, with consistent support from the Prime Minister. The campaign launched towards achieving the desired destination branding has a simple proposition of ‘GREAT Britain – You’re Invited’. It has been designed to increase the number of travellers visiting the nation as well as build the aspiration value of travelling to the United Kingdom. Other concomitant effects of the resulting increase in visitors would obviously be purely economic with positive impacts on revenue and employment levels of the country. This particular marketing campaign will be analysed on the basis of the aforementioned literature review on the subject.